2008
DOI: 10.1136/adc.2007.133512
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of atopy in children with chronic constipation

Abstract: In our study group, prevalence of atopy among children with CC is similar to that in the general population. The level of refraction of CC does not seem to be related to cow's milk allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
2
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 21 publications
0
37
2
9
Order By: Relevance
“…There are no studies regarding this variable on functional constipation. Cow's milk intolerance can lead on to constipation according to Iacono et al, [19], but Simeone et al, found no relation between cow's milk and constipation [20]. In our present study also there was no significant difference among those who had cow's milk and those who did not.…”
Section: Discussioncontrasting
confidence: 38%
“…There are no studies regarding this variable on functional constipation. Cow's milk intolerance can lead on to constipation according to Iacono et al, [19], but Simeone et al, found no relation between cow's milk and constipation [20]. In our present study also there was no significant difference among those who had cow's milk and those who did not.…”
Section: Discussioncontrasting
confidence: 38%
“…Moreover, evidence of increased eosinophil and mast cell infiltration at rectal biopsy, which improves after a restricted diet [11,12], is suggestive of the causal association between CMA and constipation. The study of Simeone et al [24] and other published studies do not agree with this hypothesis, but they are few and the populations of observed children are poor.…”
Section: Discussioncontrasting
confidence: 46%
“…Studies of children with refractory constipation fail to demonstrate any improvement after a period of elimination of milk from the diet. This suggests that constipation is not caused by cow's milk ingestion, and there is no clinical support for eliminating it from the diet [25].…”
Section: Therapymentioning
confidence: 96%